Pelatihan Olahan Produk Makanan Berbahan Dasar Jamur Dalam Rangka Penguatan dan Ketahanan Ekonomi Masyarakat Perkotaan Bagi Anggota Kelompok Tani “Elok Mekar Sari - Tri Andjarwati; Hwihanus Hwihanus; Pramita Studiviany Soemadijo (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The results of mushroom cultivation are processed by members of the "Elok Mekar Sari" Farmers Group into innovative processed products with high selling value, such as Mushroom Satay, Mushroom Sempol, Mushroom Tofu Walik, Krispi Mushrooms, Mushroom Sandwiches, Mushroom Topping Pizza and various other mushroom preparations.Some of the problems faced by the "Elok Mekar Sari" Farmers Group are lack of access to information about mushroom processing technology, availability of raw materials due to geography, economics, environment, technological and regulatory factors and demand. Apart from that, there are difficulties with available markets, public understanding of the benefits of mushrooms and the types that can be processed and consumed as an addition to a nutritious diet.Hands-on training methods and mentoring with the mushroom community in Surabaya who will teach how to grow and care for mushrooms and how to process them into various food products with high nutritional value with solutions Providing access to information and training on mushroom processing technology, increasing the availability of raw materials quality through oyster mushroom cultivation and development programs, support for promotion and marketing of mushroom products produced through the marketplace and development of communication campaigns aimed at increasing public understanding and awareness of the benefits of mushrooms and the types that can be processed and consumed